2002
DOI: 10.1063/1.1431279
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrodynamic theory of nonresonant Raman spectra in liquids: Fifth-order spectra

Abstract: The third-and fifth-order nonlinear Raman response of liquid CS 2 calculated using a finite field nonequilibrium molecular dynamics method Building upon the framework of the preceding paper, a molecular hydrodynamic theory of the fifth-order ͑two-dimensional͒ nonresonant Raman spectrum in a simple liquid is presented. A multi-time mode-coupling-like theory is developed and compared with recent computer simulations for liquid Xe. The theory is able to provide a microscopic rationale for the absence of an echo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Instead of carrying out a long equilibrium MD simulation, one can perform a number of independent nonequilibrium MD simulations by exerting impulsive forces onto the Raman-active modes in a given liquid. , Then, the fifth-order Raman response function calculated by averaging over a number of nonequilibrium MD trajectories was doubly Fourier-transformed to obtain the 2D Raman spectrum. Instead of molecular liquids, simple liquids were theoretically considered in detail and the fifth-order Raman response function was calculated by using a mode-coupling theory, and the results were directly compared with MD simulations. Recently, a hybrid equilibrium/nonequilibrium MD simulation method for calculating the fifth-order Raman response function was theoretically proposed and used to calculate the 2D Raman spectra of liquid Xe, CS 2 , and water for the sake of direct comparisons with previous theoretical and experimental results . Despite the successes of these theoretical and computational efforts of simulating fifth-order Raman response functions of molecular and simple liquids, a complicating difficulty was rather found in experiments.…”
Section: 1 Fifth-order Raman Scattering Spectroscopymentioning
confidence: 99%
“…Instead of carrying out a long equilibrium MD simulation, one can perform a number of independent nonequilibrium MD simulations by exerting impulsive forces onto the Raman-active modes in a given liquid. , Then, the fifth-order Raman response function calculated by averaging over a number of nonequilibrium MD trajectories was doubly Fourier-transformed to obtain the 2D Raman spectrum. Instead of molecular liquids, simple liquids were theoretically considered in detail and the fifth-order Raman response function was calculated by using a mode-coupling theory, and the results were directly compared with MD simulations. Recently, a hybrid equilibrium/nonequilibrium MD simulation method for calculating the fifth-order Raman response function was theoretically proposed and used to calculate the 2D Raman spectra of liquid Xe, CS 2 , and water for the sake of direct comparisons with previous theoretical and experimental results . Despite the successes of these theoretical and computational efforts of simulating fifth-order Raman response functions of molecular and simple liquids, a complicating difficulty was rather found in experiments.…”
Section: 1 Fifth-order Raman Scattering Spectroscopymentioning
confidence: 99%
“…Without at least one of these two sources, no fifth-order Raman signal can exist. It was expected that in most liquids each of these sources will contribute to the signal, and early work in the field indicated it should be possible to separate the effects of the two contributions. , Over the years, intense theoretical efforts have used a variety of approaches to simulate the fifth-order Raman response of various systems, including multimode Brownian oscillator models, ,, harmonic oscillator models, normal-mode theory, molecular dynamics simulations, hydrodynamic theory, the generalized Langevin equation, classical time correlation functions, and finite-field molecular dynamics simulations. In several cases, this has required the development of new theories and computational approaches, with previous theories having proved inadequate at properly describing the liquid state. Collectively, the theoretical work in this area has demonstrated that the fifth-order Raman response is very sensitive to the details of the intermolecular potential and treatment of the liquid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the peak appearing in R ͑5͒ ͑t 2 , t 1 ͒ is not necessarily located on the t 1 = t 2 axis. 39 In fact, we can estimate that the peak position in Fig. 1͑a͒ is ͑t 2 , t 1 ͒ = ͑0.77, 0.64͒ by using a parabolic interpolation.…”
Section: R Smentioning
confidence: 99%
“…10,11 A very large body of theoretical works on 2D Raman and IR spectroscopies have been devoted to the study of inhomogenity, 2,12 anharmonicity, 10,13,14 rotational motion, 15 vibrational dephasing, 11,[16][17][18][19][20] inter-and intramo-lecular interactions, [21][22][23] nonlinear system-bath coupling, 11,16 conformal change, 24,25 initial condition, 26,27 phase matching conditions, 28 and chemical reactions. 29 Molecular-dynamics ͑MD͒ simulations have been performed ranging from liquids [30][31][32][33][34][35][36][37][38][39][40] to more complex molecules such as peptides. [41][42][43] 2D Raman spectroscopies are advantageous in studying molecular dynamics in condensed phases because Raman pulses can create instantaneous vibrational excitations on the molecular system and their coherence can be detected by spectroscopic means.…”
Section: Introductionmentioning
confidence: 99%